The Application of Duckweed Liquid Organic Fertilizer to Cell Populations in the Culture of Nannochloropsis oculata - Ariany, Nina; Mustahal, .; Syamsunarno, Mas Bayu (Hasanuddin University, 2021)
Nannochloropsis oculata is one of the single-celled microalgae that has been commonly cultured in the marine fish culture sector as zooplankton feed which has high nutritional content. To support growth and reproduction, the availability of nutrients in N. oculata culture media needs to be considered. This study aims to determine the effect of the best liquid organic fertilizer (POC) duckweed (L. minor) on cell population growth in N. oculata culture. The method used in this research is an experimental method using Completely Randomized Design (CRD) with 5 treatments, namely P0 (TSP 10 mg + ZA 40 mg + urea 45 mg) as a control treatment, P1 (POC duckweed 5%), P2 (POC duckweed 10%), P3 (POC duckweed 15%), and P4 (POC duckweed 20%) were repeated 3 times in each treatment. The initial density of N.oculata cells was 2 x 106 cells/ml in a culture media volume of 1000 ml. Growth was observed every day for 14 days. The results showed that the POC concentration of 10% duckweed can be used as an alternative to inorganic fertilizers (TSP, ZA, and urea) because it can increase cell population growth by 30.92 ± 1.84 cells/ml at the peak of the exponential phase, as well as the value of the growth rate. cells 0.38 ± 0.03 cells / ml / day and cell generation time of 43.88 ± 3.24 hours were not significantly different (p> 0.05) with P0 treatment (TSP, ZA, and urea). The range of water quality parameters in the culture media during the study were temperature 25-33oC, pH 4.89-8.40, salinity 25-38.33 ppt, and DO 4.07-7.27 ml / l. The measured value of water quality in culture media was still within the tolerance limits of N. oculata cells so that cells could still grow and divide.